Potential for neural regeneration after neurotoxic injury in the adult mammalian retina - Sotaro Ooto; Tadamichi Akagi; Ryoichiro Kageyama; Joe Akita; Michiko Mandai; Yoshihito Honda; Masayo Takahashi (2004)
It has long been believed that the retina of mature mammals is incapable of regeneration. In this study, using the N -methyl- d -aspartate neurotoxicity model of adult rat retina, we observed that some Müller glial cells were stimulated to proliferate in response to a toxic injury and produce bipolar cells and rod photoreceptors. Although these newly produced neurons were limited in number, retinoic acid treatment promoted the number of regenerated bipolar cells. Moreover, misexpression of basic helix–loop–helix and homeobox genes promoted the induction of amacrine, horizontal, and rod photoreceptor specific phenotypes. These findings demonstrated that retinal neurons regenerated even in adult mammalian retina after toxic injury. Furthermore, we could partially control the fate of the regenerated neurons with extrinsic factors or intrinsic genes. The Müller glial cells constitute a potential source for the regeneration of adult mammalian retina and can be a target for drug delivery and gene therapy in retinal degenerative diseases.